Yeast Oral Delivery of DAF16 shRNAs Results in Effective Gene Silencing in C. elegans - Benedetta Caraba; Arianna Montanari; Emily Schifano; Fabiana Stocchi; Giovanna Costanzo; Daniela Uccelletti; Cristina Mazzoni (Current Issues in Molecular Biology)
Plant Parasitic Nematodes (PPNs) are a major problem in agriculture. Damage caused by PPNs has been estimated at USD 80–157 billion annually. The estimates could be even worse in the future in the context of a growing world population in a climate change scenario and with the removal/reduction in the use of some nematodicides due to the strong ecological impact. Biocontrol Agents (BCAs) currently constitute only 8.8% of the general pesticide market. With a view to an ecological transition, the transition from pesticides to biopesticides represents an important challenge that appears necessary not only for organic farming, but also in so-called integrated agriculture. Among the possible BCAs, microorganisms, and in particular yeast, which enjoys the GRAS (Generally Recognized As Safe) status, have the advantage of being able to be produced on a large scale by fermentation on waste substrates at low cost. In this paper, as proof of concept we constructed yeast strains expressing short hairpin RNAs (shRNAs) targeting the daf-16 gene in C. elegans. We demonstrate that oral ingestion of yeast cells expressing DAF16 shRNA is efficient in lowering daf-16 expression and lifespan, suggesting a sustainable RNA interference-based strategy to inhibit the development of PPNs.